Amide-based diarylmaleimide derivatives and polymers: Highly selective and ratiometric fluorescence sensing for anions. (February 2015) - Lin, Zhenghuan; Ma, Yingshuang; Zheng, Xin; Huang, Limei; Yang, E.; Wu, Cheng-Ya; Chow, Tahsin J.; Ling, Qidan
Abstract: A series of diarylmaleimide derivatives and polymers based on amide group were designed and synthesized to detect anions selectively and sensitively. Three bisindolylmaleimide derivatives (FAM-p, FAM-m and FAM-o) employing trifluoroacetamide as receptor exhibited strong fluorescent quenching upon fluoride and cyanide. Trifluoroacetamide receptor was replaced by acetamide to obtain other two derivatives (AM-p and AM-o) which showed higher selectivity than FAMs with sensing for only fluoride. The diarylmaleimide derivatives were introduced into the backbone of polyfluorene by Suzuki reaction to prepare polymer PFAM and PAM with same sensing selectivity for anions as FAM and AM, respectively. PFAM and PAM were found to be ratiometric fluorescence sensors for a fluorescence resonance energy transfer (FRET) from fluorene segments to diphenylmaleimide units. The experimental and DFT/TDDFT calculation results demonstrated that the interaction mechanism of FAMs with F − and CN − was hydrogen bond interaction and nucleophilic addition reaction, respectively. Graphical abstract: Highlights: The novel fluorescent sensors based on amide showed high selectivity for F − and CN − . The interaction for F − and CN − was hydrogen bond and addition reaction, respectively. The selectivity was improved further by replacing trifluoroacetamide with acetamide. The sensitivity was improved further by introducing sensors into polyfluorene. The copolymers exhibited ratiometric fluorescence properties upon F − or CN − .